PENGEMBANGAN GROUP INVESTIGATION DENGAN PERMAINAN â€œAKU SEORANG DETEKTIFâ€ KELAS IV SD MUHAMMADIYAH 1 MALANG - Arisinta, Renika; Wicaksono, Bayu Hendro; Utami, Ima Wahyu Putri (Program Studi Pendidikan Guru Sekolah Dasar Universi, 2017)
Abstract: The type of research conducted is Research and Development (RnD). In this research aiming to produce product development of Group Investigation(GI) learning modelwith game